2017
DOI: 10.1186/s12962-017-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Costs and savings associated with a pharmacists prescribing for minor ailments program in Saskatchewan

Abstract: BackgroundHealth care systems around the world have started to develop pharmacists prescribing for minor ailments (PPMA) programs. These programs aim to improve the efficiency of care, reduce physician visits, and increase the accessibility to prescription medication (Rx). This study performed an economic impact analysis of the pharmacists prescribing for minor ailments program in Saskatchewan.MethodsWe measured costs for the program and the alternative scenario (i.e. no PPMA program) from a public payer and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 38 publications
0
44
0
4
Order By: Relevance
“…Community pharmacy already provides a range of commissioned clinical services that contribute to improved patient outcomes, are effective (in terms of process measures), cost‐effective (when comparing the cost of community pharmacy with other providers) (Murray, ; Watson et al., ; Wright, ) and offer direct savings in terms of other health services avoided (such as GP and emergency department visits) (Ramalho de Oliveira, Brummel, & Miller, ). Recent estimates that community pharmacy could safely treat more than 10% of general practice and 5% of emergency department consultations (Fielding et al., ), at a substantially lower cost (Baqir, Learoyd, Sim, & Todd, ; Watson et al., ), and growing evidence that pharmacies can feasibly and appropriately improve access to treatment in particular for low‐income groups (Rafferty, Yaghoubi, Taylor, & Farag, ), suggest that community pharmacies have a place in the healthcare system for providing primary healthcare for certain common, self‐limiting or uncomplicated conditions efficiently and at scale (Bell, Dziekan, Pollack, & Mahachai, ; Curley et al., ; Watson et al., ), although uptake of services remains low and suggests that lack of awareness among patients may restrict the impact on health systems of community pharmacy services (Eades, Ferguson, & O'Carroll, ; Saramunee et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacy already provides a range of commissioned clinical services that contribute to improved patient outcomes, are effective (in terms of process measures), cost‐effective (when comparing the cost of community pharmacy with other providers) (Murray, ; Watson et al., ; Wright, ) and offer direct savings in terms of other health services avoided (such as GP and emergency department visits) (Ramalho de Oliveira, Brummel, & Miller, ). Recent estimates that community pharmacy could safely treat more than 10% of general practice and 5% of emergency department consultations (Fielding et al., ), at a substantially lower cost (Baqir, Learoyd, Sim, & Todd, ; Watson et al., ), and growing evidence that pharmacies can feasibly and appropriately improve access to treatment in particular for low‐income groups (Rafferty, Yaghoubi, Taylor, & Farag, ), suggest that community pharmacies have a place in the healthcare system for providing primary healthcare for certain common, self‐limiting or uncomplicated conditions efficiently and at scale (Bell, Dziekan, Pollack, & Mahachai, ; Curley et al., ; Watson et al., ), although uptake of services remains low and suggests that lack of awareness among patients may restrict the impact on health systems of community pharmacy services (Eades, Ferguson, & O'Carroll, ; Saramunee et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The total annual estimated cost avoidance of pharmacist prescribing TPN services for neonates was (5,109.33 USD) and with a discount of Table 2). The total annual estimated cost avoidance of pharmacist providing TPN services for pediatrics was (11,817.09 USD) and with a discount of 10-20%, it was (10,635.38-9453.67 USD). The total annual estimated cost avoidance of pharmacist providing TPN services per hospital for pediatrics was (24,225.05 USD) and with a discount of 10-20%, it was (21,802.55-19,380.04 USD), whereas monthly estimated cost avoid-ance was (1,053.26 USD) and with a discount of 10-20%, it was (947.93-842.61 USD) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported lower costs than that of this study. 11 This might be because TPN services were newly established with pharmacist as the prescriber. The estimated cost avoidance of pharmacist prescribing TPN was underestimated because most of the cost avoidance was recorded for the personal cost, which is related to salary only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations